Neurofilament Light Chain in Cerebrospinal Fluid and Blood in Multiple System Atrophy: A Systematic Review and Meta-Analysis - Silvia Demiri; Dimitra Veltsista; Vasileios Siokas; Kanellos C. Spiliopoulos; Antonia Tsika; Polyxeni Stamati; Elisabeth Chroni; Efthimios Dardiotis; Ioannis Liampas (Brain Sciences)
Background/Objectives: Multiple system atrophy (MSA) presents a challenging diagnosis due to its clinical overlap with other neurodegenerative disorders, especially other α-synucleinopathies. The main purpose of this systematic review and meta-analysis was to assess neurofilament light chain (NfL) differences in the CSF and blood of patients with MSA versus the healthy control group (HC), patients with Parkinson’s disease (PD) and patients with Lewy body dementia (LBD). Secondarily, the diagnostic metrics of CSF and circulating NfL in MSA versus HC, PD, LBD, progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) were discussed. Methods: MEDLINE and EMBASE were thoroughly searched for relevant case-control studies. Standardized mean differences (SMDs) were calculated separately for CSF and blood NfL per comparison. Statistical heterogeneity was assessed based on the Q and I^2 statistics. Results: Twenty-five relevant studies were retrieved. Quantitative syntheses revealed elevated CSF and circulating NfL levels in individuals with MSA versus HC [SMD = 1.80 (95%CI = 1.66, 1.94) and SMD = 2.00 (95%CI = 1.36, 2.63), respectively] versus PD [SMD = 1.65 (95%CI = 1.26, 2.03) and SMD = 1.63 (95%CI = 0.84, 2.43), respectively] as well as versus LBD [SMD = 1.17, (95%CI = 0.71, 1.63) and SMD = 0.65 (95%CI = 0.30, 1.00), respectively]. Diagnostic accuracy was outstanding for CSF and blood NfL in MSA versus HC and PD, and it was moderate in MSA versus LBD. On the other hand, it was suboptimal in MSA vs. PSP and CBD. Conclusions: Both CSF and circulating NfL levels are elevated in MSA compared to HC, PD and LBD. To achieve optimal diagnostic properties, further work is required in the standardization of processes and the establishment of reference NfL intervals and/or thresholds.